2002
DOI: 10.1254/jjp.89.337
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factors and Drugs in the Brain

Abstract: ABSTRACT-In mammalian cells, protein de novo synthesis is mainly regulated at the stage of gene transcription by RNA polymerase II in the nucleus. Transcription factors are proteins that bind to the specific nucleotide sequences at promoter or enhancer regions on target genes to control the transcription of mRNA from genomic DNA. In this article, we have outlined the signal responsiveness of different transcription factors to particular drugs in the brain. Nuclear transcription factors rapidly respond to a var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
3
0
1
Order By: Relevance
“…The central portion of the protein contains 86 = 30 + 28 + 28 aa decomposed into 3 zinc fingers with the following secondary structure (letter H is for the α-helix segment, letter E is for the β-sheet segment and letter C is for the random coil segment) CCCEECCCCCCCCEECHHHHHHHHHHHHHH CCCEECCCCCCEECHHHHH-HHHHHHHHH CCCEECCCCCCEECHHHHHHHHHHHHHC Taking the former 3-letter chain as the relation of a finitely generated group on 3 letters (and rank 2), we get the cardinality sequence for the cc of its subgroups as [1,3,7,26,112, 717, • • • ], which fits the cardinality sequence of cc of subgroups of the free group F 2 only up to the index 4.…”
Section: The Dna-binding Domain Egr1mentioning
confidence: 99%
See 1 more Smart Citation
“…The central portion of the protein contains 86 = 30 + 28 + 28 aa decomposed into 3 zinc fingers with the following secondary structure (letter H is for the α-helix segment, letter E is for the β-sheet segment and letter C is for the random coil segment) CCCEECCCCCCCCEECHHHHHHHHHHHHHH CCCEECCCCCCEECHHHHH-HHHHHHHHH CCCEECCCCCCEECHHHHHHHHHHHHHC Taking the former 3-letter chain as the relation of a finitely generated group on 3 letters (and rank 2), we get the cardinality sequence for the cc of its subgroups as [1,3,7,26,112, 717, • • • ], which fits the cardinality sequence of cc of subgroups of the free group F 2 only up to the index 4.…”
Section: The Dna-binding Domain Egr1mentioning
confidence: 99%
“…AAGGAAATTT[1,3,7,26,195, 1692, 11803, 73192 • • • ] ., A AR GTGGAAGATT [1, 3, 7,34, 139, 931, 5208, 43867 • • • ] Table 7 in [15], A . CCACGACCCG [1,7, 20, 167, 754, 7232, 60860, 683597 • • • ]…”
mentioning
confidence: 99%
“…Gene transcription would therefore lead to long-lasting and sometimes permanent alterations of a variety of cellular functions through consolidation of transient extracellular signals following regulation of de novo biosynthesis of inducible target proteins (8). Such a consolidation mechanism would be operative in certain situations including neuronal plasticity and degeneration in the CNS (9). We have recently shown that brief exposure to static magnetic fields leads to a marked but transient increase in DNA binding of the nuclear transcription factor activator perotein-1 (AP1) responsible for the recognition of the nucleotide sequence TGACTCA in cultured rat hippocampal neurons, with concomitant exacerbation of the ability of NMDA to increase intracellular free Ca 2+ levels as determined by fluorescence imaging (10).…”
Section: Introductionmentioning
confidence: 99%
“…a. aufgrund der komplexen Interaktionen alle relevanten Monoamine und andere Neurotransmitter beeinflussen kann, die b. über Autorezeptoren Rückwirkungen auf die eigene Transmission besitzt und c. unter anderem über "second messenger" -offenbar verzögert -Prozesse im Zellinneren anstößt[93,94], die im Erfolgsfall zu einer Remission beitragen.Dabei unterscheiden sich Patienten offenbar in ihrer Sensibilität für spezifisch serotoninerge bzw. grundsätzlich für monoaminerge Interventionen[95]; ein Erfolg der Therapie ist allerdings nicht Ausdruck davon, dass vorher ein Serotoninmangel vorgelegen haben muss[96].…”
unclassified